A Systematic Review: Formulation of Facial Wash Containing Essential Oil - Cut Puspita Salsabila Syaharani; Nadia Isnaini; Essy Harnelly; Vicky Prajaputra; Siti Maryam; Fadli A. Gani (Universitas Syiah Kuala, 2023)
Facial wash is a major need of the community because it is very helpful in removing dirt, dust, dead skin cells, oil, residual cosmetics and provides moisture to the skin. In general, the face wash used by the community is classified as a synthetic product that can damage the skin, one alternative to avoid this by using natural ingredients such as essential oils. Essential oils have many benefits, including as anti-acne, antibacterial, and antioxidant. Therefore, a systematic review was conducted regarding the formulation of essential oils as a face wash that can be a reference in future research. The systematic review method was carried out by collecting data from various literature sources obtained from several research journals that have been published both nationally and internationally accredited reviewing face wash cosmetics containing essential oils. Based on the systematic review, it was found that there are several face wash formulations containing essential oils of patchouli oil, tea tree oil, jasmine oil, cinnamon oil, black cumin seed oil, basil oil, ylang-ylang oil, peppermint oil, turmeric oil, lemongrass oil, lavender oil, and tangerine oil.